2021
DOI: 10.9758/cpn.2021.19.3.530
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Erythropoietin and Erythropoietin Receptors Levels in Children with Attention Deficit Hyperactivity Disorder

Abstract: Objective: Attention deficit hyperactivity disorder (ADHD) is a heterogeneous, highly heritable, a common childhood neurobehavioural disorder resulting from complex gene-gene and gene-environment interactions. The erythropoietin (Epo)/erythropoietin receptors (EpoR) system turned out to have additional important functions in nonhematopoietic tissue. In this study, we aimed to investigate the levels of Epo and and EpoR, and also their diagnostic values in children with ADHD. Methods: A total of 70 children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It also regulates genes associated with angiogenesis, erythropoiesis, iron metabolism, glucose metabolism, cell proliferation, cell survival, and apoptosis, in addition to its contribution to VEGF effects (Semenza, 1998). It is further evidence that HIF-1a contributes to the pathogenesis of ADHD that these processes differ between persons with ADHD and healthy people (Gungor et al, 2021;Scassellati et al, 2020) . Although it has been shown that the development of ADHD may be linked to conditions such as hypoxia and ischemia, which are peripheral manifestations of HIF-1a, to our knowledge there is no study explicitly examining HIF-1a levels in ADHD patients (Miguel et al, 2015;Ohshima et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…It also regulates genes associated with angiogenesis, erythropoiesis, iron metabolism, glucose metabolism, cell proliferation, cell survival, and apoptosis, in addition to its contribution to VEGF effects (Semenza, 1998). It is further evidence that HIF-1a contributes to the pathogenesis of ADHD that these processes differ between persons with ADHD and healthy people (Gungor et al, 2021;Scassellati et al, 2020) . Although it has been shown that the development of ADHD may be linked to conditions such as hypoxia and ischemia, which are peripheral manifestations of HIF-1a, to our knowledge there is no study explicitly examining HIF-1a levels in ADHD patients (Miguel et al, 2015;Ohshima et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, intensive research efforts have focused on GAD, applying neuroimaging, genetic, and blood-based approaches toward discovery of pathogenetic and treatment-related biomarkers [ 1 ]. Currently studies on biological markers in the human blood such as G protein-coupled estrogen receptor-1, oxidative stress, testosterone, dehydroepiandrosterone sulfate and cortisol performed to determine peripheral markers [ 2 - 5 ]. Plasma appears to be a rational source for proteomic and metabolomic measurements because it is easily accessible and because several molecules from the brain are transported across the blood-brain barrier and reach the circulation.…”
Section: Introductionmentioning
confidence: 99%